2017
DOI: 10.1186/s12944-016-0402-5
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models of atherosclerosis: a historical perspective and recent advances

Abstract: Atherosclerosis represents a significant cause of morbidity and mortality in both the developed and developing countries. Animal models of atherosclerosis have served as valuable tools for providing insights on its aetiology, pathophysiology and complications. They can be used for invasive interrogation of physiological function and provide a platform for testing the efficacy and safety of different pharmacological therapies. Compared to studies using human subjects, animal models have the advantages of being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 176 publications
4
108
0
1
Order By: Relevance
“…Notably, since the structural integrity of the artery wall is compromised also in the surrounding area of atherosclerotic plaques, we analyzed the regions adjacent to the lesion, and also in this case, we observed high frequencies of Tregs. In order to obtain fresh murine atherosclerotic plaques for our studies, we took advantage of ApoE-KO mice treated with aldosterone-so far, the elective mouse model for this disease (58). Our aim, using this experimental model of atherosclerosis, was merely to obtain samples to analyze from an immunologic point of view, and therefore, we did not compare our results with wt non-atherosclerosis vessels, from which we could not extract any infiltrating cells to relate.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, since the structural integrity of the artery wall is compromised also in the surrounding area of atherosclerotic plaques, we analyzed the regions adjacent to the lesion, and also in this case, we observed high frequencies of Tregs. In order to obtain fresh murine atherosclerotic plaques for our studies, we took advantage of ApoE-KO mice treated with aldosterone-so far, the elective mouse model for this disease (58). Our aim, using this experimental model of atherosclerosis, was merely to obtain samples to analyze from an immunologic point of view, and therefore, we did not compare our results with wt non-atherosclerosis vessels, from which we could not extract any infiltrating cells to relate.…”
Section: Discussionmentioning
confidence: 99%
“…Since the dominant cholesterol carrier in mice is high density lipoprotein (HDL) 66,67 , wild type C57BL/6J mice are resistant to the development of atherosclerosis, necessitating the use of knockout animals to model atherosclerosis 68 . Using Apoe -/- and Ldlr -/- mice, it has been demonstrated that hypercholesterolemia results in the entrapment and modification of lipoproteins in the subendothelial space, which initiates the recruitment of inflammatory monocytes 50,69 .…”
Section: Inflammation and Metabolic Diseasesmentioning
confidence: 99%
“…Atherosclerosis (AS) underlies most cardiovascular diseases, is characterized by the accumulation of lipids and the proliferation of fibrous materials, proliferation of arterial smooth muscle cells, and chronic inflammatory cells. [103][104][105] miR-33 has potent effects on autophagy and lysosomal function that reinforce its targeting of cholesterol efflux and reverse cholesterol transport gene pathways to mediate cholesterol homeostasis. miR-33 inhibition in atherosclerotic mice restores defective autophagy in the aorta and macrophages of atherosclerotic plaques.…”
Section: Mirs Regulate Autophagy In Atherosclerosismentioning
confidence: 99%